Finding my voice [compact disc, unabridged] : my journey to the West Wing and the path forward - Jarrett, Valerie, 1956- (Penguin Audio, 2019)
Valerie Jarrett shares her journey as a daughter, mother, lawyer, business leader public servant, and leader in government at an historic moment in American history, the longest serving senior advisor in the Obama White House.